El poder constituyente en el primer constitucionalismo hispano - Portillo, José M. (Anuario de Historia de América Latina, 2018)
Historiography usually takes constituent power as a sort of monolithic, extraordinary power that is able to generate a new political and social order. If generally speaking this approach is correct, the experience of the first constitutionalism in the Spanish Atlantic contributes to refine this perception. In this essay I analyze how this power was more effective in the field of the ius gentium, that is, when it came to define national sovereignty than in the field of inner public right, that is, in relation with social, domestic an ethnic order.
Keywords: Constituent Power; Hispanic Constitutionalism; Fuero; Nation